Hermitian (ϵ,δ)-Freudenthal-Kantor Triple Systems and Certain Applications of *-Generalized Jordan Triple Systems to Field Theory - Noriaki Kamiya; Matsuo Sato (Advances in High Energy Physics)
We define Hermitian (ϵ,δ)-Freudenthal-Kantor triple systems and prove a structure theorem. We also give some examples of triple systems that are generalizations of the u(N)⊕u(M) and sp(2N)⊕u(1) Hermitian 3-algebras. We apply a *-generalized Jordan triple system to a field theory and obtain a Chern-Simons gauge theory. We find that the novel Higgs mechanism works, where the Chern-Simons gauge theory reduces to a Yang-Mills theory in a certain limit.